1991
DOI: 10.1002/gepi.1370080204
|View full text |Cite
|
Sign up to set email alerts
|

Can dietary intake patterns account for the familial aggregation of disease? Evidence from adult siblings living apart

Abstract: The familial aggregation of certain chronic diseases is well documented [Perkins, 1986; King et al., 1984; Anderson, 1982]. Dietary data on adult brothers living apart were used to examine whether familial clustering of disease could be explained by nature or nutriture. Intakes of nutrients were strikingly more similar among siblings than expected: when correlations were adjusted for country of residence, 21 of 25 (84%) were statistically significant. Thus, dietary patterns among adult siblings are more alike … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

1993
1993
2005
2005

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 18 publications
1
8
0
Order By: Relevance
“…However, we also considered analyses that account for possible nonindependence of effects, realizing that lifestyle and medical behaviors may be correlated among individuals within the same family (22,23). This was carried out using repeated measures ANOVA for continuous behaviors, and generalized estimating equation methodology for categorical variables.…”
Section: Methodsmentioning
confidence: 99%
“…However, we also considered analyses that account for possible nonindependence of effects, realizing that lifestyle and medical behaviors may be correlated among individuals within the same family (22,23). This was carried out using repeated measures ANOVA for continuous behaviors, and generalized estimating equation methodology for categorical variables.…”
Section: Methodsmentioning
confidence: 99%
“…Risk factors for many diseases including coronary heart diseases occur within families (Sellers et al, 1991;Perkins, 1986;Austin et al, 1987). While suggestive of a genetic effect, families who live in the same environment also share cultural, behavioral and occupational factors that may also be related to disease risks.…”
Section: Introductionmentioning
confidence: 99%
“…Regardless, there are data to suggest that some aspects of childhood diet may be maintained into adulthood. Sellers et al [1991] have shown that nutrient intakes of adult brothers living apart are more similar than expected on the basis of common culture. Similarly, Oliveria et al [1992] have demonstrated that dietary patterns of adults are established early in life.…”
Section: Introductionmentioning
confidence: 87%